The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1523/jneurosci.22-12-04860.2002
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Modulation of Dendritic K+ Channels in Hippocampus Involves a Mitogen-Activated Protein Kinase Pathway

Abstract: We investigated mitogen-activated protein kinase (MAPK) modulation of dendritic, A-type K+ channels in CA1 pyramidal neurons in the hippocampus. Activation of cAMP-dependent protein kinase A (PKA) and protein kinase C (PKC) leads to an increase in the amplitude of backpropagating action potentials in distal dendrites through downregulation of transient K+ channels in CA1 pyramidal neurons in the hippocampus. We show here that both of these signaling pathways converge on extracellular-regulated kinases (ERK)-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
290
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(307 citation statements)
references
References 53 publications
(85 reference statements)
14
290
0
3
Order By: Relevance
“…An emerging model suggests that activated ERK1/2 participate in several pathways that work together to induce synaptic plasticity (English and Sweatt, 1997;Lamprecht and LeDoux, 2004). Thus, ERK1/2 modulate back-propagating action potentials by phosphorylating dendritic A-type K + channels (Kv4.2 subunits) (Watanabe et al, 2002;Yuan et al, 2002;Morozov et al, 2003), and is one of several signaling cascades shown to initiate local protein synthesis after synaptic activation through phosphorylation of translation factors (eIF4E) and ribosomal protein S6 (Kelleher et al, 2004a(Kelleher et al, , 2004b). …”
Section: Discussionmentioning
confidence: 99%
“…An emerging model suggests that activated ERK1/2 participate in several pathways that work together to induce synaptic plasticity (English and Sweatt, 1997;Lamprecht and LeDoux, 2004). Thus, ERK1/2 modulate back-propagating action potentials by phosphorylating dendritic A-type K + channels (Kv4.2 subunits) (Watanabe et al, 2002;Yuan et al, 2002;Morozov et al, 2003), and is one of several signaling cascades shown to initiate local protein synthesis after synaptic activation through phosphorylation of translation factors (eIF4E) and ribosomal protein S6 (Kelleher et al, 2004a(Kelleher et al, , 2004b). …”
Section: Discussionmentioning
confidence: 99%
“…MEK directly phosphorylates and activates ERK (Crews and Erikson, 1992), whereas PKA and PKC regulate ERK activity by indirect, MEK-dependent (Yuan et al, 2002) or MEKindependent mechanisms (Grammer and Blenis, 1997;Kinkl et al, 2001). Similarly, extensive intracellular crosstalk between hippocampal PKA, PKC, and MEK converging at ERK was shown in hippocampal slices (Roberson et al, 1999) and in vivo (Ahi et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Neuromodulators strongly regulate these channels through phosphorylation, association with auxiliary subunits, and expression-level control. A-type potassium channels modulate the action potential broadening, b-AP (backpropagation of action potentials), spike generation, and integration of synaptic inputs (Ramakers and Storm 2002;Watanabe et al 2002;Yuan et al 2002;Birnbaum et al 2004;Lauver et al 2006;Hammond et al 2008;Kim and Hoffman 2008). Among the A-type potassium channels, the Kv4 channels adjust dendritic function by limiting spike-timing-dependent plasticity.…”
mentioning
confidence: 99%